PENERAPAN PROSEDUR AUDIT TERHADAP AKUN BEBAN OPERASIONAL PT MEP OLEH KAP DJOKO, SIDIK & INDRA - Teguh Prayogo Aditya (2022)
The importance of financial statements in a company requires a company to have reliability in order to achieve maximum profit for a business. Public Accounting Firm Djoko, Sidik & Indra is a business entity that provides services in the field of services to evaluate financial statements in accordance with generally accepted auditing standards. PT MEP is one of the clients of KAP Djoko, Sidik & Indra. In the process of implementing the audit process, KAP Djoko, Sidik & Indra apply audit procedures to be part of the reference and planning during the audit. Operating expenses are economic sacrifices made by a company for the continuity of company activities. This activity is related to the company's profit so it is necessary to carry out an adequate audit. Based on the results of the audit, it shows that all recordings in the operating expense account have been carried out fairly in all material respects.